Low-cost vertical taper for highly efficient light in-coupling in bimodal nanointerferometric waveguide biosensors. (15th February 2019) - Grajales, Daniel; Fernández Gavela, Adrián; Domínguez, Carlos; Sendra, Jose Ramón; Lechuga, Laura M
Abstract: There is still the need for a compact and cost-effective solution for efficient light in-coupling in integrated waveguides employed in photonic biosensors, especially when these waveguides are of submicron dimensions and operate at visible wavelengths. The employment of a vertically stacked taper with a larger input area is proposed to meet this need. The design of the taper is divided into two stages: in the first stage, light is guided downwards by two vertically stacked tapers; in the second stage, an inverted taper directly confines the light inside the waveguide. The design parameters are optimized using commercial software, obtaining a total theoretical light coupling efficiency of 72.25%. The taper is manufactured using SU-8 polymer as the main material, employing standard photolithography techniques at wafer level. After characterization, the results show the practicality of the taper when coupling light from macrometric sources to nanometric waveguides, obtaining an experimental coupling efficiency of 55%. With this vertical taper, a compact, easy-to-couple and cost-effective solution is achieved for waveguide-based biosensors operating at visible wavelengths, opening the way for a truly portable point-of-care biosensor for low-cost and label-free diagnostics.